Apriori Algorithm Application for Consumer Purchase Patterns Analysis - Situmorang, Boldson Herdianto; Isra, Ali; Paragya, Dhatu; Akbar Adhieputra, David Aulia (Komputasi: Jurnal Ilmiah Ilmu Komputer dan Matematika, 2024)
The Apriori algorithm is a data mining association rule algorithm for finding relationship patterns between one or more items in a dataset. Apriori algorithm is often used in transaction data analysis or market basket analysis. Apriori algorithm is used to find out consumer purchase patterns in e-commerce systems and provide product recommendations to consumer by extaracting associations or events from transactional data. This study is purposed for deeply analyze the steps, performance of Apriori algorithm, and give relevant an example of case study to better explain the steps of Apriori algorithm application, as well as the results achieved.